Recent Development of Cancer Vaccines - Dong, Yanwen (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Immunotherapy, a truly innovative method in the field of cancer treatment, has attracted a great deal of attention because of its potential to bring about a revolution in the outcomes of cancer therapies. Even though there are many different ways being studied to make immunotherapy even more effective, fully realizing its potential, especially when it comes to cancer vaccines, is still a difficult goal to achieve. This review goes into detail about the different types of cancer vaccines, explaining the basic biological processes behind them and how they work with the immune system to fight cancer. We divide cancer vaccines into three main groups: virus-like particle (VLP) vaccines, peptide vaccines, and DNA/mRNA vaccines. Furthermore, this review also covers how these vaccines are being used in a wide range of infectious diseases and cancer types, emphasizing their versatility and the potential positive effects they can have on patients. Additionally, important topics related to the future of cancer vaccination are discussed, such as new ways to store vaccines to keep them effective, ways to reduce safety concerns, and the creation of personalized vaccines that are tailored to each patient’s specific needs and cancer characteristics. By facing these challenges head-on and embracing the latest technologies, we hope to fully unlock the power of cancer vaccines, pushing the boundaries of cancer immunotherapy even further.